A Model of Stochastic Equilibrium in a Quasi-Competitive Industry - Sutton, John (Review of Economic Studies, 1980)
Considerable attention has been devoted in recent years to the study of markets which are quasi-competitive in the sense that they retain the notion of a large number of firms selling a homogeneous product, but depart from perfect competition in relaxing the assumption that consumers are perfectly informed as to the prices of the various firms. The initial surge of interest in this type of model was motivated by the need, first noted by Arrow (1956), to deal with the firm, even in a competitive environment, as a price setter, in order adequately to tackle the analysis of disequilibrium behaviour. Thus early work in the field, beginning with Fisher ((1970), (1972), (1973)) focussed on the question of whether an initial market distribution of prices would, over time, converge to a unique equilibrium price. More recent work has, however, developed the idea that market equilibrium might be characterized by a persistent distribution of prices. That this is more reasonable in the light of the variety and volatility of prices (which is) the commonplace of our experience was argued by Rothschild (1973). A further, and theoretically more compelling, reason for exploring this question, however, is provided by what is probably the most striking aspect of the literature on these markets: the fact that for a very wide range of apparently quite reasonable assumptions, the distribution of prices converges to the monopoly price (Diamond (1971), Hey (1974)). Indeed, where prices do converge, they converge to the competitive price only under very strong conditions: for example, where firms are artificially constrained to behave as if they were perfect competitors (Fisher, Rothschild, op. cit.). Thus it would seem that in order to tackle the question of whether, under conditions of imperfect price information, any competitive features of the market may be preserved, we are compelled to examine market equilibria of this more general class. Such price dispersion as is empirically observed in many markets undoubtedly owes its origin to a wide range of contributory factors. This suggests representing the firm as experiencing a succession of exogenous random shocks, as in Lucas and Prescott (1974). An alternative approach is to explore the possibility that firms set a range of suboptimal prices via their various estimates of actual demand conditions, as deduced by following an optimal estimation procedure (stopping rule), as explored by Rothschild (1974). More germane to our present concerns as to whether the range of actual prices, or their average, might be drawn by competitive pressures below the monopoly price, is the more recent work which begins from the notion that consumers differ in their costs of acquiring information, so that firms partition themselves permanently into subgroups patronized predominantly by different mixtures of consumer types; the better informed consumers being associated, as it were, with the lower price firms . (Salop and Stiglitz (1978), Axell (1977).) The present model adopts a rather different type of approach; we aim to model equilibrium in the quasi-competitive economy as an ongoing process, in which firms continually compete with each other to increase their respective sales to a number of identical customers.